Challenging Patriarchy through Feminist Praxis in Cisneros’s Only Daughter - Karki, Govinda Bahadur (KMC Research Journal, 2025)
Sandra Cisneros’s Only Daughter presents a Mexican-American woman’s negotiation of identity and creative activities within patriarchal and culturally conservative - indigenous social structures. This research addresses the issues of marginalization, silencing, and identity loss experienced by women within patriarchal societies particularly through the lens of Chicana and intersectional feminism, as well as other feminist theorists. This study analyzes how Cisneros transforms personal experience and memory into feminist praxis. The narrative becomes a weapon of resistance against patriarchy reclaiming voice and subjectivity. The primary objectives of this research are to specifically focus on how intersecting identities affect the formation and expression of women’s identities and voicelessness within patriarchal systems. Using qualitative textual analysis with descriptive research design, the study explores how Cisneros disrupts patriarchal language aligning with Écriture féminine and the concepts of other feminist theorists. The findings reveal that Only Daughter operates as a feminist and decolonial intervention. This study holds significant value both in its practical application and scholarly contribution to feminist literary discourse. Academically, this research contributes to the evolving field of feminist literary studies by offering an original interpretation that blends theory with textual analysis.